Identifikasi Penggunaan Chat GPT Pada Esai TOEFL Menggunakan Metode Long Short Term Memory - Karina Natasya Darmawan; Silvester Dian Handy Permana; Ketut Bayu Yogha Bintoro (Bulletin of Computer Science Research, 2026)
The use of Artificial Intelligent (AI) technology is increasing along with technological developments. One of the technologies that is often used is Chat GPT (Generative Pre-trained Transformers). Chat GPT is an application used for many things such as source of information, write an essay, and answer TOEFL essay questions. Because of its easiness, people will excessively use this that can cause people to lose creativity because they do not understand the material context and rely too much on the AI text result, which poses academic risks. Teachers also have difficulty to distinguish between AI and human text writing. Therefore, this research is to identify whether TOEFL essay are result of human text or GPT. This research used the Long Short Term Memory (LSTM) method to identify the use of GPT in TOEFL essay. This research also used 3 different split data configurations to find the best results. This research consists of 2 TOEFL essay datasets with the same prompt and has total of 220 data samples. The LSTM method is a modification of algorithm Recurrent Neural Network (RNN) and part of Deep Learning. The LSTM method involves memory cell controlled by three gates, such as input gate, forgot fate, output gate, and the hidden state. The gates are used to decide and control the information added, deleted, and removed from memory cell. The results of this research is a system that can help teachers detect the use of GPT in TOEFL essay. This research successfully identified the use of GPT in TOEFL essay in a 70:30 data split configuration with a loss score of 25,07%, accuracy score of 89,83%, and prediction score of 64,32%. Therefore, it is hoped that this system can help teachers identify the use of GPT and facilitate the assessment of TOEFL essay.